2022
DOI: 10.1039/d1tc03519c
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive mechano-optical strain sensors based on 2D materials for human wearable monitoring and high-end robotic applications

Abstract: Recently, myriad stretchable flex sensors have been developed based on the principle of changing piezo resistance, capacitance and impedance. However, these approaches suffer from cyclic stability, poor hysteresis, relatively lower...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Since 2011, the MXene family’s explosive expansion has provided insight into the advancements in thermoelectric devices, batteries, supercapacitors, membranes, and photothermal conversion (PTC). Because MXenes have a special mix of hydrophilic surfaces and strong electrical conductivity, they outperform conventional 2D materials in both basic and practical applications. Applications for gas sensing have also been made with recently developed 2D MXenes . MXene is a promising option for biosensing applications because to its favorable metallic conductivity, optical absorbance, mechanical stability, increased heterogeneous electron transfer rate, and strong redox capacity.…”
Section: State-of-the-art 2d Sensing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2011, the MXene family’s explosive expansion has provided insight into the advancements in thermoelectric devices, batteries, supercapacitors, membranes, and photothermal conversion (PTC). Because MXenes have a special mix of hydrophilic surfaces and strong electrical conductivity, they outperform conventional 2D materials in both basic and practical applications. Applications for gas sensing have also been made with recently developed 2D MXenes . MXene is a promising option for biosensing applications because to its favorable metallic conductivity, optical absorbance, mechanical stability, increased heterogeneous electron transfer rate, and strong redox capacity.…”
Section: State-of-the-art 2d Sensing Materialsmentioning
confidence: 99%
“…It has been demonstrated that proof-of-concept strain sensors can track various states, such as the start and progression of crazes. 2D MoS 2 and its composites are considered among the best options for applications involving tiny thin-film strain sensors due to their exceptional qualities. , Applications for strain sensors based on 2D materials may be found in wearable electronics, robotics, medical devices, and structural health monitoring.…”
Section: Sensing Properties Of 2d Materialsmentioning
confidence: 99%
“…Any deformation of the object being observed causes a change in the structure of the sensor, which leads to a change in the electrical response of the sensor [1]. Flexible strain sensors are widely used in smart robots, electronic skin, and wearable devices [2][3]. The most common structure for flexible strain sensors is carbon-based nanomaterials combined with various polymers.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of intelligent materials and micronano manufacturing technologies, flexible strain sensors are increasingly prominent in health monitoring, 1 electronic skin, 2 human-machine interfaces, 3 soft robots, 4 and implantable electronics. 5 Especially in the field of wearable electronic devices, flexible strain sensors have incomparable advantages over traditional rigid sensors, such as softness, bending resistance, and stretchability.…”
Section: ■ Introductionmentioning
confidence: 99%